PEMBERIAN KOTORAN KAMBING TERHADAP PERTUMBUHAN DAN HASIL WORTEL (Daucus carota) DAN BAWANG DAUN (Allium fistulosum L.) DENGAN BUDIDAYA TUMPANGSARI - Trias Budi Rahayu; Bistok Hasiholan Simanjuntak; - Suprihati (Agric, 2014)
Intercropping cultivation model is commonly used in organic farming system. The system is aimed to save land and fertilizer aside from creating biodiversity in a portion of a planting. The research was conducted in Permata Hati Farm, Ciburial Village, Cisarua Sub district, Bogor Regency, West Java from October 2012 to January 2013. The purposes of the research are: a) to know the effect of goat dung application toward the growth and yield of organically managed carrot and scallion intercropping, and b) to determine the best quantity of goat dung to promote growth and yield of carrot and scallion intercropping. Randomized Completely Block Design (RCBD) with 6 treatments and 3 replications was used in this experiment. The treatments applied were 0 ton ha- 1, 5 ton ha-1, 10 ton ha-1, 15 ton ha-1, 20 ton ha-1, and 25 ton ha-1 of goat dung. Duncan’s Multiple Range Test (DMRT) at the confidence level of 95% was used to analyze the result. The application of 15 ton ha-1 goat dung affected scallion’s height and number of seedlings as well as carrot’s biomass and height. This dosage resulted in the best yield of scallion and carrot intercropping.